Penerapan Metode Vikor pada Pengambilan Keputusan Seleksi Prajurit TNI AD untuk Pendidikan Bintara - Heru Sutejo; Patmawati Hasan (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research aims to implement the VIKOR method as a Decision Support System (DSS) in the selection process of Indonesian Army (TNI AD) soldiers for advanced Bintara education. The challenges faced include the underutilization of technology in the selection process, limited computerized selection results, and the use of printed documents that may slow down the process. The research method employs a developmental approach to DSS based on the Simon model with stages of intelligence, design, choice, and implementation. The study is conducted at Kodam XVII/Cenderawasih, focusing on health, physical fitness (garjas), academic, and psychological criteria for selection. Blackbox testing is carried out to ensure the success of the DSS application in managing criteria, alternatives, and subcriteria. The results show consistency between the DSS application and MS Excel in VIKOR method calculations.